Blind detection of cyclostationary signals based on multi‐antenna beamforming technology. Issue 19 (5th October 2021) - Wang, Jie; Gao, Rui; Ye, Ding; Zhang, Zhenghua
Abstract: Cyclostationary feature detection is one of the widely used spectrum sensing techniques. Its greatest advantage is that it can effectively separate the signal from the noise under the condition of a low signal‐noise ratio (SNR). Although cyclostationary feature detection is not affected by noise uncertainty like energy detection (ED), conventional cyclic stationary feature detection needs to know the prior conditions of signal cycle frequency (CF), cycle period, and so on. Moreover, the communication signals of authorized users are generally weak, which greatly affects the detection efficiency of cyclic stationary features. Therefore, this paper proposes a blind detection technique of cyclostationary characteristics based on conventional beam synthesis multi‐antenna. The principle is to enhance the signal receiving intensity of the antenna by using beamforming technology, and realize the blind detection of cyclostationary signals by forming the direction of arrival angle. Not only that, the authors also make full use of the Wilk's approximation theorem and the generalized likelihood ratio test (GLRT) to derive the detection probability and false alarm probability. The simulation results show that the proposed cyclic stationary signal detector based on beam synthesis multi‐antenna can realize blind detection of unknown cycle signals in a low SNR environment.